2020
DOI: 10.1371/journal.pbio.3000738
|View full text |Cite
|
Sign up to set email alerts
|

The M-current works in tandem with the persistent sodium current to set the speed of locomotion

Abstract: The central pattern generator (CPG) for locomotion is a set of pacemaker neurons endowed with inherent bursting driven by the persistent sodium current (INaP). How they proceed to regulate the locomotor rhythm remained unknown. Here, in neonatal rodents, we identified a persistent potassium current critical in regulating pacemakers and locomotion speed. This current recapitulates features of the M-current (IM): a subthreshold noninactivating outward current blocked by 10,10-bis(4-pyridinylmethyl)-9(10H)-anthra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 100 publications
1
35
1
Order By: Relevance
“…In our interpretation of the genotype-phenotype relationship through the prism of KCNQ2/3 heteromers, one caveat is that our current knowledge on KCNQ2 and KCNQ3 mRNA and protein colocalization stems from work primarily performed in sympathetic neurons and in neurons in the neocortex and hippocampus, with only limited information on subcortical regions (see e.g., [64][65][66]), spinal cord [67,68], and the peripheral nervous system [45]. In the hippocampus and cortex, KCNQ2 and KCNQ3 colocalization in excitatory and inhibitory cells is highly prevalent, with very few exceptions.…”
Section: Beyond the Forebrainmentioning
confidence: 99%
See 1 more Smart Citation
“…In our interpretation of the genotype-phenotype relationship through the prism of KCNQ2/3 heteromers, one caveat is that our current knowledge on KCNQ2 and KCNQ3 mRNA and protein colocalization stems from work primarily performed in sympathetic neurons and in neurons in the neocortex and hippocampus, with only limited information on subcortical regions (see e.g., [64][65][66]), spinal cord [67,68], and the peripheral nervous system [45]. In the hippocampus and cortex, KCNQ2 and KCNQ3 colocalization in excitatory and inhibitory cells is highly prevalent, with very few exceptions.…”
Section: Beyond the Forebrainmentioning
confidence: 99%
“…Most notably, KCNQ3 channels were highly enriched in polymodal nodose ganglion cells, whereas KCNQ2 was enriched in Piezo2-expressing nodose neurons, which are important for sensing pulmonary volume and stretching (https://ernforsgroup.shinyapps.io/vagalsensoryneurons/). Additionally, a recent report showed that KCNQ2 channels are enriched in neurons important for locomotion in the spinal cord [68], a finding similar to a previous work that found robust expression of KCNQ2 but of KCNQ3 in spinal cord neurons [67, 68]. The differential enrichment of KCNQ2 channels over KCNQ3 channels in the brainstem and some vagus neurons may also contribute to the very different symptoms exhibited by patients carrying Kcnq2 and Kcnq3 gain-of-function mutations [7].…”
Section: Introductionmentioning
confidence: 99%
“…PICs were measured in voltage clamp by injecting a slow depolarizing voltage ramp (10 mV/s from -90 to -10 mV) over 8 seconds 20,118,121 . PIC onset voltage, voltage at which the peak current occurs (voltage peak), peak current amplitude, and peak current density were measured from post-hoc leaksubtracted traces as in 20,118,122 .…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…Indeed, Kcnq2 deletion or expression of KCNQ2 pathogenic variants in neurons leads to elevated excitability, typically manifested as a higher number of action potentials and reduced spike frequency adaptation. Such changes in excitability occur in multiple brain regions, including the hippocampus and neocortex, and across multiple cell types ( Peters et al, 2005 ; Singh et al, 2008 ; Soh et al, 2014 , 2018 ; Verneuil et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%